Liquid Phase Chemical Deposition of High Tech ZnSe Thin Flims - Pingale, P. C.; Mane, S. T.; Lendave, S. A.; Kamble, S. S.; Suryawanshi, R. V.; Singh, Arvind; Kothari, D. C.; Deshmukh, L. P.; Sharon, M. (Journal of Nepal Chemical Society, 2013)
Being a promising and potential candidate for optoelectronic device applications, zinc selenide thin films were obtained for the first time on the glass microslides using a liquid phase chemical bath deposition. The deposition conditions, such as bath temperature (70 0C), deposition time (210 mins.), reaction pH (10.5± 0.2) and quantity of hydrazine hydrate (reducing agent) were finalized and the possible growth mechanism and reaction kinetics have been suggested. As the ZnSe films grow well in strong reducing atmosphere, the quantity of hydrazine hydrate was varied from 2 ml to 15 ml and ZnSe samples were obtained. The final product ZnSe thin films are physically hard, tightly adherent, relatively uniform and diffusely reflecting with light brown colored tinge in smoky appearance. An EDS analysis showed that the film stoichiometry depends on quantity of the added reducing agent in the bath. Structural studies were carried out on these films by an X-ray diffraction technique using Cukα radiation. It appeared that the ZnSe films are hexagonal wurtzite in structure with preferred orientation along <101>. The calculated d-values, intensities of reflections and lattice parameters matched with that of the JCPD data. The calculated particle size decreased with quantity of hydrazine hydrate added in the bath (decrease in Zn/Se ratio). The optical absorption measurements in the range of wavelength from 300-1100 nm showed direct type of transitions with an optical gap decreased from 2.71 eV to 2.60 eV for the change of Zn/Se ratio from 0.993 to 0.571. The surface features revealed by SEM showed that the crystallites are nonuniformly distributed and spherical in shape. From micrographs it is seen that crystallite size decreased with increasing amount of hydrazine hydrate. Some overgrowth like structures (of the same size and shapes) has also been observed at high concentration of hydrazine hydrate. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9384 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 130-137 Uploaded date: 12/20/2013